Coplanar different-end stearic acid-titanium dioxide Janus sheet and preparation method thereof
By modifying titanium dioxide sheets with stearic acid, the formation of homogeneous heretostearic acid-titanium dioxide Janus sheets, the problem of limited application of titanium dioxide in water-oil heterogeneous system is solved, and efficient wastewater treatment and catalytic activity are achieved , especially under light, the degradation effect on organic matter is significant.
Patent Information
- Application Number
- CN202411292597.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2024-12-17
AI Technical Summary
The existing titanium dioxide materials are difficult to degrade oil-soluble pollutants in water-oil heterogeneous systems, and nanomaterials are prone to agglomeration and poor dispersion, resulting in limited application in wastewater treatment.
The titanium dioxide sheet is modified with stearic acid to form an isoside stearic acid-titanium dioxide Janus sheet, which is prepared by sol-gel, solvent heat and impregnation methods to achieve uniform size of the material, no stacking and thorough modification. Enhance its stability and catalytic activity at the water-oil interface.
It achieves efficient degradation of p-nitrobenzene, has stronger emulsification ability and catalytic activity, and can exist stably in the water-oil interface under light, significantly improving the efficiency and reusability of wastewater treatment.
Smart Images

Figure CN119140079A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photocatalysis, in particular to a isoplanar isotropic stearic acid-titanium dioxide Janus flake and a preparation method thereof. Background Art
[0002] With the acceleration of the global industrialization process, wastewater treatment has become an urgent problem to be solved in the field of environmental protection. Using photocatalysts to remove organic / inorganic pollutants in wastewater under light conditions has become one of the main research directions. Researchers are committed to developing photocatalysts with high catalytic activity and low secondary pollution. Among many photocatalysts, titanium dioxide (TiO2) has become the preferred material in the field of wastewater treatment due to its strong oxidation ability, stable chemical properties, and non-toxicity. However, wastewater is mostly a water-oil heterogeneous system. Titanium dioxide materials with strong hydrophilicity are difficult to degrade oil-soluble pollutants in water-oil heterogeneous systems. In addition, the disadvantages of titanium dioxide nanomaterials such as easy agglomeration and poor dispersibility also seriously limit the application of titanium dioxide materials in water-oil heterogeneous systems.
[0003] Surface modification of titanium dioxide nanomaterials can solve the problem of easy agglomeration and poor dispersibility of titanium dioxide in water phase. It can also make it possible to contact with the oil phase in a heterogeneous system (wastewater) through organic modification. Janus amphiphilic modification is to graft a modifier on one side of the nanomaterial, while the other side remains unmodified, thereby forming an anisotropic structure with half hydrophilic and half oleophilic on the same material. Conventional Janus flakes are obtained by modifying one side of the flakes, using ultrasonic treatment to break the flakes, and obtaining small-sized Janus flakes. However, after ultrasonic treatment, this method has the disadvantages of uneven size of the flakes, easy stacking and agglomeration, and poor stability at the interface of the water-oil heterogeneous system. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a simple preparation method, the flakes have uniform size, no stacking phenomenon, more thorough modification, higher catalytic activity for the degradation of nitrobenzene, and reusable isoplanar stearic acid-titanium dioxide Janus flakes and a preparation method thereof.
[0005] The technical solution of the present invention is:
[0006] A homoplanar heteroterpenic stearic acid-titanium dioxide Janus flake is characterized in that: the homoplanar heteroterpenic stearic acid-titanium dioxide Janus flake is a Janus flake obtained by modifying one end of the titanium dioxide flake surface with stearic acid and leaving the other end unmodified.
[0007] Furthermore, the sizes of the isoplanar stearic acid-titanium dioxide Janus flakes are relatively uniform.
[0008] A method for preparing isoplanar heterotropic stearic acid-titanium dioxide Janus flakes, the specific preparation process is as follows:
[0009] (1) Preparation of vertically grown titanium dioxide thin film-glass substrate
[0010] Titanate sol II is prepared using ethyl titanate, isopropyl titanate or tetrabutyl titanate as a titanium source; a titanium dioxide thin film glass substrate is horizontally placed in the inner tank of a polytetrafluoroethylene reactor, reacted at 150°C for 12 hours, naturally cooled, washed, and dried to obtain a vertically grown titanium dioxide thin film glass substrate;
[0011] (2) ultrasonically dispersing stearic acid into anhydrous ethanol to prepare a stearic acid-anhydrous ethanol mixed solution, wherein the mass volume ratio of stearic acid to anhydrous ethanol is 3:200 g / mL, heating to 70°C, and then horizontally placing the vertically grown titanium dioxide thin film-glass substrate in the stearic acid-anhydrous ethanol mixed solution, reacting at 70°C for 10 hours, cooling, washing with water and alcohol, drying at 60°C for 3 hours, and peeling off to obtain isoplanar heterotropic stearic acid-titanium dioxide Janus thin films.
[0012] Furthermore, the preparation process of the titanate sol II is:
[0013] At 35°C, concentrated hydrochloric acid was added to glacial acetic acid at a volume ratio of 40:1. After reacting for 10 minutes, a titanium source was added dropwise at a volume ratio of 200:(10-23) between glacial acetic acid and the titanium source. The titanium source was ethyl titanate, isopropyl titanate or tetrabutyl titanate. Stirring was continued for 30 minutes, and then the temperature was raised to 40°C to form a sol to obtain titanate sol II.
[0014] Furthermore, the preparation process of the titanium dioxide thin film glass substrate is:
[0015] Titanate sol I is prepared using ethyl titanate, isopropyl titanate or tetrabutyl titanate as a titanium source. Titanate sol I is coated on a glass substrate, dried, reacted in an air atmosphere at 500°C in a muffle furnace for 2 hours, and then cooled naturally.
[0016] Furthermore, the preparation process of the titanate sol I is:
[0017] a. Prepare an ethanol solution by volume ratio of 35:6 with anhydrous ethanol and deionized water;
[0018] b. At 25°C, glacial acetic acid and concentrated hydrochloric acid were added to anhydrous ethanol while stirring in a volume ratio of 35:4:1. After reacting for 20 minutes, a titanium source was added dropwise in a volume ratio of 35:(10-33) of anhydrous ethanol to a titanium source, and stirring was continued for 20 minutes. Finally, the ethanol solution of step a was added dropwise in a volume ratio of 41:10 of an ethanol solution to tetrabutyl titanate to form a sol to obtain a titanate sol I.
[0019] Furthermore, the mass ratio of the titanate sol I, the titanate sol II and stearic acid is 1:40:3.
[0020] Beneficial effects of the present invention:
[0021] (1) A novel type of isotropic Janus titanium dioxide flakes (V-STA-TiO2 JNs) with one end hydrophilic and the other end lipophilic was prepared by simple sol-gel, solvothermal and impregnation methods. The operation is simple and the prepared Janus flakes have uniform size, no stacking phenomenon, more thorough modification, high catalytic activity for the degradation of nitrobenzene under simulated light, and can be reused.
[0022] (2) By partially (one end) modifying the titanium dioxide flakes, V-STA-TiO2 JNs have amphiphilic properties, which allows them to stably exist at the water-oil interface and can be used as an emulsifier to prepare Pickering emulsions. Since the new Janus flakes (V-STA-TiO2 JNs) are vertically embedded in the water-oil interface, they have stronger emulsification ability and catalytic activity than traditional Janus flakes (STA-TiO2 JNs) that are horizontally attached to the water-oil interface. The Pickering emulsion prepared by V-STA-TiO2 JNs remains relatively stable after 40 days.
[0023] (3) After stearic acid modification, V-STA-TiO2 JNs have stronger visible light response ability compared with titanium dioxide sheets (V-TiO2-TiO2 sheets). Therefore, under the premise of being able to stably exist at the heterogeneous water-oil interface, more active species can be produced under light to degrade organic pollutants. The modified Janus material has stronger photocatalytic activity than titanium dioxide material. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is a graph showing the relationship between the photodegradation efficiency of nitrobenzene and time of the titanium dioxide flakes prepared in the present invention (corresponding to Example 1, Comparative Example 1 and Comparative Example 2);
[0025] Figure 2is a SEM image of the isoplanar stearic acid-titanium dioxide Janus flakes (V-STA-TiO2JNs) of the present invention (corresponding to Example 1);
[0026] Figure 3 is a SEM image of the anti-modified conventional titanium dioxide Janus flakes (STA-TiO2 JNs) of the present invention (corresponding to Example 1);
[0027] Figure 4 is a SEM image of the titanium dioxide sheets (V-TiO2-TiO2 sheets) of the present invention (corresponding to Example 2);
[0028] Figure 5 The infrared curves of the raw material stearic acid of Example 1, the titanium dioxide flakes after the titanium dioxide flake-film peeling treatment vertically grown on the glass substrate, the isotropic stearic acid-titanium dioxide and the conventional Janus flakes modified on the opposite side of Comparative Example 1 are shown in FIG.
[0029] Figure 6 These are polarizing microscope images of the isotropic stearic acid-titanium dioxide Janus flakes (a) of the present invention (corresponding to Example 1) and the opposite-face modified conventional Janus flakes (b) (corresponding to Example 1);
[0030] Figure 7 The photographs show the emulsion stabilizing ability of the isomorphous stearic acid-titanium dioxide Janus flakes (1) of the present invention (corresponding to Example 1) and the opposite-face modified conventional Janus flakes (2) (corresponding to Example 1) at different times (Fig. a. 20 days, Fig. b. 40 days);
[0031] Figure 8 It is the UV-visible diffuse reflectance spectra of the raw material stearic acid of the present invention (corresponding to Example 1), the titanium dioxide flakes after the titanium dioxide flake-film peeling treatment vertically grown on the glass substrate, and the isoplanar stearic acid-titanium dioxide. DETAILED DESCRIPTION
[0032] The following embodiments of the present invention are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solutions of the present invention, and are therefore only examples, and cannot be used to limit the protection scope of the present invention.
[0033] Example 1
[0034] (1) Preparation of titanate sol Ⅰ
[0035] (a) 35.0 mL of anhydrous ethanol (volume concentration 99.7%) and 6.0 mL of deionized water were added to a 100 mL beaker and stirred at 25° C. for 10 min to obtain an ethanol solution;
[0036] (b) 35.0 mL of anhydrous ethanol (volume concentration 99.7%) was added to a 150 mL flask, and the flask was placed in a constant temperature water bath at 25° C. and stirred at 300 r / min. Then, 4.0 mL of glacial acetic acid (volume concentration 99.5%) and 1.0 mL of concentrated hydrochloric acid (volume concentration 36-38%) were slowly added to the flask. After reacting for 20 min, 10.0 mL of tetrabutyl titanate was dropwise added to the above mixture, and stirring was continued for 20 min. Finally, the ethanol solution prepared in step (a) was dropwise added to the flask through a constant pressure funnel. After reacting for a period of time, after an obvious Tyndall effect appeared, titanate sol I was obtained;
[0037] (2) Preparation of Titanate Sol II
[0038] Add 200.0mL of glacial acetic acid (volume concentration of 99.5%) to a 500mL flask, and place the flask in a constant temperature water bath at 35°C and stir at 300r / min. Then add 5.0mL of concentrated hydrochloric acid (volume concentration of 36-38%) to the flask. After reacting for 10 minutes, add 10.0mL of tetrabutyl titanate dropwise to the above mixture and continue stirring for 30 minutes. Finally, raise the temperature to 40°C. After the obvious Tyndall effect appears, titanate sol II is obtained.
[0039] (3) Preparation of titanium dioxide thin film glass substrate
[0040] 1.5 g of titanate sol I was coated on a glass substrate (width × length: 26 mm × 76 mm). After the titanate sol I was completely dried, it was placed in a muffle furnace in an air atmosphere at 500° C. for 2 h. After natural cooling, a titanium dioxide thin film glass substrate was obtained.
[0041] (4) Preparation of vertically grown titanium dioxide thin film glass substrate
[0042] The titanium dioxide thin film glass substrate was horizontally placed in the inner tank of a 100 mL polytetrafluoroethylene reactor, and then 60 g of titanate sol II was slowly added into the inner tank, and the reaction was carried out at 150°C for 12 hours. After natural cooling, the glass substrate was taken out, and the glass substrate was washed with water and alcohol for many times to remove the unreacted organic matter on the surface, and finally dried at 60°C for 2 hours to obtain a vertically grown titanium dioxide thin film glass substrate;
[0043] (5) Preparation of isomeric stearic acid-titanium dioxide Janus flakes
[0044] 3.0 g of stearic acid (STA) was ultrasonically dispersed in 200.0 mL of anhydrous ethanol (volume concentration 99.7%). After the stearic acid (STA) was completely dispersed, the mixed solution was heated to 70°C, and then the vertically grown titanium dioxide thin film glass substrate was horizontally placed in the above mixed solution and reacted for 10 hours. After natural cooling, the glass substrate was washed with water and alcohol for many times to remove the unreacted stearic acid on the surface, and finally dried at 60°C for 3 hours to obtain a vertically grown stearic acid thin film-titanium dioxide glass substrate; after peeling, isoplanar heterotropic stearic acid-titanium dioxide Janus flakes (V-STA-TiO2 JNs) were obtained.
[0045] Example 2
[0046] The preparation method of titanate sol I and titanate sol II is the same as that in Example 1, except that the titanium source is replaced by isopropyl titanate from tetrabutyl titanate, and the amount of titanium source used in the preparation of the two sols is increased to 15 mL respectively. Other experimental conditions, steps and reagent amounts remain unchanged.
[0047] Example 3
[0048] The preparation method of titanate sol I and titanate sol II is the same as that in Example 1, except that the titanium source is replaced by ethyl titanate from tetrabutyl titanate, and the amount of titanium source used in the preparation of the two sols is increased to 23 mL respectively. Other experimental conditions, steps and reagent amounts remain unchanged.
[0049] Example 4
[0050] The preparation method of titanate sol I and titanate sol II is the same as that of Example 1, except that concentrated hydrochloric acid is replaced by concentrated nitric acid (68%), and other experimental conditions, steps and reagent amounts remain unchanged.
[0051] Comparative Example 1
[0052] (1) 3.0 g of stearic acid (STA) was ultrasonically dispersed in 200.0 mL of anhydrous ethanol (99.7%). After the stearic acid (STA) was completely dispersed, the temperature was raised to 70° C. to obtain a mixed solution;
[0053] (2) The titanium dioxide thin film glass substrate in step (3) of Example 1 was placed horizontally in the mixed solution of step (1) and reacted for 10 hours. After natural cooling, the glass substrate was washed with water and alcohol for multiple times to remove unreacted stearic acid on the surface, and then dried at 60°C for 3 hours. Finally, the modified thin film was peeled off from the glass substrate, and after ultrasonic treatment, the anti-modified traditional titanium dioxide Janus thin film (STA-TiO2 JNs) was obtained.
[0054] Comparative Example 2
[0055] In step (4) of Example 1, the titanium dioxide flake-film vertically grown on the glass substrate is subjected to a peeling treatment to obtain titanium dioxide flakes (V-TiO2-TiO2 sheets).
[0056] 1. Study on the physical and chemical properties of isoplanar stearic acid-titanium dioxide Janus flakes
[0057] (1) Photocatalytic performance analysis
[0058] A Pickering emulsion of nitrobenzene, water and a photocatalyst was prepared. The photocatalytic activity of the isotropic stearic acid-titanium dioxide Janus sheets (V-STA-TiO2 JNs), the antipodal modified conventional stearic acid-titanium dioxide Janus sheets (STA-TiO2 JNs) and the titanium dioxide sheets (V-TiO2-TiO2 sheets) prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention as photocatalysts for degradation of nitrobenzene under visible light was evaluated, and the specific steps were as follows:
[0059] 48.0 mL of deionized water, 12.0 mL of nitrobenzene and 1.0 g of photocatalyst were added to a flask with an outer wall wrapped with tin foil, and stirred at 3500 r / min for 3 min to obtain a Pickering emulsion, which was allowed to stand for 30 min to ensure that the adsorption-desorption of the oil phase on the emulsifier surface reached equilibrium, and then a degradation reaction was carried out under a xenon lamp (300 W) light source with a wavelength of 200-1100 nm. During the reaction, 1.0 mL of the suspension was drawn every 10 min. After centrifugation, the supernatant was pretreated and the absorbance of the liquid was tested with a TU-1900 UV-visible spectrophotometer, and the change in nitrobenzene concentration was calculated to obtain its photodegradation rate.
[0060] The relationship between the photodegradation efficiency of nitrobenzene and time of different samples is shown in the figure Figure 1 As shown in the degradation diagram of nitrobenzene by isoplanar heterocyclic stearic acid-titanium dioxide Janus flakes (V-STA-TiO2 JNs), it can be seen that the time required for nitrobenzene degradation to 50% is 22 minutes, while the time required for the opposite modified traditional stearic acid-titanium dioxide Janus flakes (STA-TiO2 JNs) is 27 minutes, and the titanium dioxide flakes (V-TiO2-TiO2 sheets) require about 90 minutes. The new Janus material completes the same degradation effect in a shorter time, and the catalytic time is shortened by nearly 5 minutes compared with the traditional Janus composite material, indicating that the new Janus material has better catalytic performance.
[0061] (2) Material structure analysis
[0062] The SEM image of the isoplanar stearic acid-titanium dioxide Janus flakes (V-STA-TiO2 JNs) of Example 1 of the present invention is as follows: Figure 2 As shown, from Figure 2 It can be seen that the size of the flakes is relatively uniform and there is no stacking phenomenon, and there is a clear boundary on each flake, indicating that stearic acid has completed the partial (one end) modification of the titanium dioxide flakes.
[0063] The SEM image of the opposite surface modified conventional Janus flake (STA-TiO2 JNs) of Comparative Example 1 of the present invention is as follows: Figure 3 As shown, from Figure 3 It can be seen that after stearic acid modification and ultrasonic treatment, there is serious stacking and uneven size between the sheets, which will directly affect the catalytic activity of the photocatalyst. Therefore, the new V-STA-TiO2 JNs Janus flakes of Example 1 of the present invention have higher photocatalytic activity than the traditional STA-TiO2 JNs titanium dioxide Janus flakes of Comparative Example 1.
[0064] The SEM image of the titanium dioxide flakes of Comparative Example 2 of the present invention is as follows: Figure 4 As shown, from Figure 4 It can be seen that the size of the flakes is relatively uniform and there is no stacking phenomenon. However, titanium dioxide is a hydrophilic material and can only be dispersed in the water phase of the water-oil heterogeneous system, which will directly affect the photocatalytic degradation of oil-soluble pollutants. Therefore, the catalytic activity of the titanium dioxide flakes in Comparative Example 2 is significantly lower than that of the Janus materials in Comparative Example 1 and Example 1.
[0065] (3) Infrared detection of materials
[0066] The infrared spectrum of titanium dioxide flakes (Comparative Example 2) modified with stearic acid to become isomeric stearic acid-titanium dioxide (Example 1) / conventional Janus flakes (Comparative Example 1) modified with opposite faces is shown as follows: Figure 5 As shown in the infrared spectrum, the characteristic absorption peaks of stearic acid all appear in the isoplanar stearic acid-titanium dioxide Janus flakes, indicating that stearic acid has been grafted onto the titanium dioxide surface and a Janus material has been prepared.
[0067] (4) Polarized light microscopy of materials
[0068] The polarizing microscope image of the opposite surface modified Janus sheet of Example 1 of the present invention is as follows: Figure 6 As shown in (a), the polarizing microscope image of the conventional modified Janus flake of Comparative Example 1 is as follows Figure 6(b) As shown. The Janus composite material is amphiphilic and can be used as a solid emulsifier for preparing Pickering emulsions; the state of the solid catalyst at the water-oil interface was observed by polarizing microscopy. The experiment found that the isoplanar stearic acid-titanium dioxide Janus flakes exist perpendicular to the water-oil interface, while the opposite-face modified traditional Janus material is parallel to the water-oil interface.
[0069] (5) Preparation and properties of Pickering emulsion
[0070] At 25°C, an emulsifier (V-STA-TiO2 JNs, STA-TiO2 JNs) with a concentration of 2.9 wt% (mass percentage) was added to a mixed system of liquid paraffin and water (V:V=1:4), and the mixture was stirred at 3500 r / min for 3 min using a high-speed homogenizer to obtain a Pickering emulsion.
[0071] like Figure 7 As shown, 20 days later, Figure 7 In (a), the Pickering emulsion (1) composed of isoplanar heterogeneous stearic acid-titanium dioxide Janus flakes is still stable, with only a small amount of solid powder appearing at the bottom of the sample bottle, while the Pickering emulsion prepared by the oppositely modified traditional Janus material (2) has demulsified, with a large amount of solid powder appearing at the bottom of the sample bottle. After 40 days (b), the emulsion composed of isoplanar heterogeneous stearic acid-titanium dioxide Janus flakes (1) remains relatively stable, while the emulsion using the oppositely modified traditional Janus material as emulsifier (2) is completely demulsified.
[0072] This phenomenon indicates that the emulsifying ability of the isomeric stearic acid-titanium dioxide Janus flakes of Example 1 of the present invention is superior to that of the conventional Janus material modified on the opposite side of Example 1 of the present invention; Figure 7 It can be seen that the new Janus material that exists in the water-oil interface in an embedded manner has a better ability to stabilize the emulsion, and therefore has a stronger catalytic activity in the photocatalytic process.
[0073] (6) UV-visible diffuse reflectance testing of materials
[0074] from Figure 8 It can be seen that the stearic acid-modified Janus material of Example 1 of the present invention has a stronger response to visible light, and therefore has a stronger visible light response ability than the titanium dioxide flakes of Comparative Example 2 of the present invention under the same conditions, thereby generating more active species to degrade pollutants.
[0075] The above analysis shows that the isoplanar heterogeneous stearic acid-titanium dioxide Janus flakes of Example 1 of the present invention have high catalytic activity in the photocatalytic degradation process. The isoplanar heterogeneous Janus flakes effectively avoid the occurrence of stacking between flakes caused by electrostatic interaction during the preparation process, and the obtained flakes have the advantages of more uniform size and more thorough modification.
[0076] The above are only specific embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A homogeneous stearic acid-titanium dioxide Janus flake, characterized in that: The isoplanar heteroterminal stearic acid-titanium dioxide Janus flakes are Janus flakes in which one end of the titanium dioxide flake surface is modified with stearic acid and the other end is not modified.
2. The isoplanar stearic acid-titanium dioxide Janus flakes according to claim 1, characterized in that: The size of the isoplanar stearic acid-titanium dioxide Janus flakes is relatively uniform.
3. A method for preparing the isoplanar isotropic stearic acid-titanium dioxide Janus flakes as claimed in claim 1, characterized in that: The specific preparation process is as follows: (1) Preparation of vertically grown titanium dioxide thin film-glass substrate Titanate sol II is prepared using ethyl titanate, isopropyl titanate or tetrabutyl titanate as a titanium source; a titanium dioxide thin film glass substrate is horizontally placed in the inner tank of a polytetrafluoroethylene reactor, reacted at 150°C for 12 hours, naturally cooled, washed, and dried to obtain a vertically grown titanium dioxide thin film glass substrate; (2) ultrasonically dispersing stearic acid into anhydrous ethanol to prepare a stearic acid-anhydrous ethanol mixed solution, wherein the mass volume ratio of stearic acid to anhydrous ethanol is 3:200 g / mL, heating to 70°C, and then horizontally placing the vertically grown titanium dioxide thin film-glass substrate in the stearic acid-anhydrous ethanol mixed solution, reacting at 70°C for 10 hours, cooling, washing with water and alcohol, drying at 60°C for 3 hours, and peeling off to obtain isoplanar heterotropic stearic acid-titanium dioxide Janus thin films.
4. The method for preparing the isoplanar isotropic stearic acid-titanium dioxide Janus flakes according to claim 3, characterized in that: The preparation process of the titanate sol II is: At 35°C, concentrated hydrochloric acid was added to glacial acetic acid at a volume ratio of 40:
1. After reacting for 10 minutes, a titanium source was added dropwise at a volume ratio of 200:(10-23) between glacial acetic acid and the titanium source. The titanium source was ethyl titanate, isopropyl titanate or tetrabutyl titanate. Stirring was continued for 30 minutes, and then the temperature was raised to 40°C to form a sol to obtain titanate sol II.
5. The method for preparing the isoplanar isotropic stearic acid-titanium dioxide Janus flakes according to claim 3, characterized in that: The preparation process of the titanium dioxide thin film glass substrate is: Titanate sol I is prepared using ethyl titanate, isopropyl titanate or tetrabutyl titanate as a titanium source. Titanate sol I is coated on a glass substrate, dried, reacted in an air atmosphere at 500°C in a muffle furnace for 2 hours, and then cooled naturally.
6. The method for preparing the isoplanar isotropic stearic acid-titanium dioxide Janus flakes according to claim 5, characterized in that: The preparation process of the titanate sol I is: a. Prepare an ethanol solution by volume ratio of 35:6 with anhydrous ethanol and deionized water; b. At 25°C, glacial acetic acid and concentrated hydrochloric acid were added to anhydrous ethanol while stirring in a volume ratio of 35:4:
1. After reacting for 20 minutes, a titanium source was added dropwise in a volume ratio of 35:(10-33) of anhydrous ethanol to a titanium source, and stirring was continued for 20 minutes. Finally, the ethanol solution of step a was added dropwise in a volume ratio of 41:10 of an ethanol solution to tetrabutyl titanate to form a sol to obtain a titanate sol I.
7. The method for preparing the styrostearic acid-titanium dioxide Janus flakes according to claim 6, characterized in that: The mass ratio of the titanate sol I, titanate sol II and stearic acid is 1:40:3.
Citation Information
Patent Citations
Preparation of 3D Janus sponge for emulsion separation and dye adsorption
CN116408054A
Metal oxide nanofibrous materials for photodegradation of environmental toxins
US20170056873A1
Method for Preparing Molybdenum Doped Titanium Dioxide Thin Film by Sol-Gel
US20170282159A1
